2017
DOI: 10.3389/fphys.2017.01086
|View full text |Cite
|
Sign up to set email alerts
|

Superior Effects of High-Intensity Interval Training vs. Moderate Continuous Training on Arterial Stiffness in Episodic Migraine: A Randomized Controlled Trial

Abstract: Background: Migraine is associated with increased cardiovascular risk and vascular dysfunction. Since aerobic exercise can reduce cardiovascular risk, the present randomized controlled trail aimed at investigating the effects of high-intensity interval training (HIT) vs. moderate continuous exercise training (MCT) on arterial stiffness in migraine patients.Methods: Forty-eight episodic migraineurs were initially enrolled in the study. 37 patients [female: 30; age: 37 (SD: 10); BMI: 23.1 (5.2); Migraine days pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 50 publications
0
29
0
9
Order By: Relevance
“…Apart from the benefits of exercise on post‐concussive symptom resolution, outlined in detail above, a recent systemic review and meta‐analysis have shown that exercise can reduce the frequency, duration, and severity of migraine headaches 125‐128 . Additionally, exercise has been shown to be either additive (amitriptyline) or non‐inferior (topiramate) to pharmaceuticals in the management of migraine .…”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%
“…Apart from the benefits of exercise on post‐concussive symptom resolution, outlined in detail above, a recent systemic review and meta‐analysis have shown that exercise can reduce the frequency, duration, and severity of migraine headaches 125‐128 . Additionally, exercise has been shown to be either additive (amitriptyline) or non‐inferior (topiramate) to pharmaceuticals in the management of migraine .…”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%
“…Compared to moderate continuous aerobic training, high intensity interval training had a more pronounced effect on reducing migraine days and cerebrovascular outcomes, but overall, aerobic activity exerted positive effects for migraineurs 46,47 . In light of the greater conferred benefit of higher intensity physical activity, the authors concluded that the positive effects of exercise may be dependent on both type of exercise and its intensity 46 . The authors’ conclusions are consistent with our findings, given the observed differences in the strength of the stress‐migraine associations across levels of physical activity.…”
Section: Discussionmentioning
confidence: 98%
“…Using a 3‐armed RCT, Hanssen et al 46,47 examined the differential effects of aerobic activities on multiple health outcomes among episodic migraineurs. Compared to moderate continuous aerobic training, high intensity interval training had a more pronounced effect on reducing migraine days and cerebrovascular outcomes, but overall, aerobic activity exerted positive effects for migraineurs 46,47 . In light of the greater conferred benefit of higher intensity physical activity, the authors concluded that the positive effects of exercise may be dependent on both type of exercise and its intensity 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Migrénesek (3,7 nap/hó) HIIT-edzése az augmentációs index -a pulzushullám-visszaverődés -az aorta merevsége -csökkenéséhez (22-ről 14,9-re), a centrális szisztolés és diasztolés vérnyomás csökkenéséhez vezetett, nagyobb mértékben, mint az egyenletes edzés, és a migrénes napok száma csökkent [38].…”
Section: Interval Edzés Egyéb Betegségek Eseténunclassified